An H-TERT Mutated Skin Metastasis as First Occurrence in a Case of Follicular Thyroid Carcinoma - Monti, Eleonora; Dono, Mariella; Gonella, Edoardo; Spina, Bruno; Pitto, Francesca; Petrogalli, Floriana; Conte, Lucia; Ambrosetti, Eleonora; Minuto, Michele N.; Ansaldo, Gian Luca; Morbelli, Silvia; Zupo, Simona; et al. (Frontiers in Endocrinology, 2019)
Differentiated thyroid cancer arising from thyroid follicular epithelial cells is the most frequent endocrine malignancy, and skin metastases are very rare. We describe a case of a 70-year-old women with a history of an indeterminate thyroid nodule on cytology. A painless, erythematous skin nodule of about 7 mm diameter was removed from the scalp and diagnosed as a metastasis from thyroid cancer. After total thyroidectomy, a histological diagnosis of follicular thyroid cancer was made. Two cycles of radioactive iodine were performed. Both the follicular thyroid carcinoma and the metastasis were investigated for the presence of BRAF/RAS and TERT promoter mutations. The results showed that the cutaneous metastasis was BRAF wild-type and TERT promoter-mutated (position g.1,295,228 C>T); in contrast, the primary thyroid lesion was negative for both molecular markers.